(untitled) (Research, Society and Development, 2021)
Objectives: To identify through scientific evidence nursing care in the prevention and treatment of diabetic foot in the elderly from 2008 to 2017. Methodology: This study consists of a qualitative literature review research developed through the Integrative Literature Review method, and an electronic search was performed in a specialized database in health and nursing. The following databases were used: Nursing Database (BDENF), Scientific Electronic Library Online (SciELO), Latin American and Caribbean Literature on Health Sciences (LILACS). Results and Discussion: The age group shows that with age this public becomes more susceptible to chronic pathologies with the increase of the aging process. Self-care is fundamental for the prevention of foot injuries in patients with DM, being difficult to support because they require changes in habits and customs, and by the denial that the individual feels about the possibility of being affected by the complications of this disease. Conclusion: Educational practices are the greatest tool to contribute to the prevention of diabetic foot and consequent amputations, thus enabling individuals to sensitize individuals to the development of self-care skills and lifestyle change.